1997
DOI: 10.1046/j.1365-2435.1997.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathalline and size‐dependent patterns of activity in Lasallia pustulata and their possible consequences for competitive interactions

Abstract: Summary 1.In dense populations of the saxicolous lichen Lasallia pustulata the margins of adjacent thalli overlap each other in intraspecific competition for space and light. 2. In situ non-destructive monitoring of hydration-dependent potential photosynthetic activity by modulated fluorescence systems in different parts of the thallus shows that the activity is structured by a centre-to-margin gradient, with the centre of the thallus remaining active for substantially longer periods than the margins when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…The strong size dependency of independent and ecologically important variables in this study con®rms earlier ®ndings (Larson 1979(Larson , 1984Hestmark et al 1997) that size will have to be considered as an essential parameter in future ecological and physiological studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The strong size dependency of independent and ecologically important variables in this study con®rms earlier ®ndings (Larson 1979(Larson , 1984Hestmark et al 1997) that size will have to be considered as an essential parameter in future ecological and physiological studies.…”
Section: Discussionsupporting
confidence: 87%
“…A similar size dependency of drying events has previously been demonstrated for some umbilicate lichens (Larson 1984;Hestmark et al 1997) and for a globose crustose lichen (Pe rez 1997), but by no means represents a universal pattern among the lichens (Larson 1984). The short photosynthetically active period in a small and young D. plumbea thallus is not only a result of a low available water reservoir per area, but also of a distinctly higher water loss per area compared to larger thalli.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Stephenson & Rundel 1979;Golojuch & Lawrey 1988;Hesbacher et al 1996;Nybakken et al 2004;Gauslaa & McEvoy 2005). Furthermore, few physiological and ecological studies of lichens focus on the importance of thallus size (Golojuch & Lawrey 1988;Hestmark et al 1997;Gauslaa & Solhaug 1998), despite the probable importance of thallus size effects in lichen ecophysiology (Larson 1984). Golojuch & Lawrey (1988) showed that in Vulpicida pinastri, the concentration of the coloured vulpinic and pinastric acids increases with thallus size, but is not correlated with habitat factors.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors suggest that biotic interactions are among the main structuring processes within saxicolous lichen communities (e.g. Yarranton & Green 1966;Lawrey 1981;Armstrong 1982Armstrong , 1986John 1989;Hestmark 1997;Hestmark et al 1997), although the importance of this relative to other processes (e.g. responses to underlying environmental factors, historical events, disturbances of various kinds) is not known.…”
Section: Introductionmentioning
confidence: 99%